Optimal information disclosure and market outcomes - Hugo Hopenhayn; Maryam Saeedi (Theoretical Economics, 2023)
This paper addresses two central questions in markets with adverse selection: How does information impact the welfare of market participants (sellers and buyers)? Also, relatedly, what is the optimal information disclosure policy and how is it affected by the planner's relative welfare weight on sellers' surplus versus consumers' surplus? We find that as a result of improved information, prices become more strongly associated with the true quality of sellers and thus more dispersed. This will result in higher total surplus. Furthermore, we find that better information has opposing welfare effects on consumers and producers that could lead to limited disclosure depending on the social objective and market characteristics.
Keywords: D21; D47; D60; D82; L11; 330; Adverse selection; consumer surplus; information design; producer surplus